New species and phylogenetic relationships of the spider genus Coptoprepes using morphological and sequence data (Araneae: Anyphaenidae) - Barone, Mariana L.; Werenkraut, Victoria; Ramírez, Martín J. (Zootaxa, 2016)
We present evidence from the standard cytochrome c oxidase subunit I (COI) barcoding marker and from new collections, showing that the males and females of C. ecotono Werenkraut & Ramírez were mismatched, and describe the female of that species for the first time. An undescribed male from Chile is assigned to the new species Coptoprepes laudani, together with the female that was previously thought as C. ecotono. The matching of sexes is justified after a dual cladistics analysis of morphological and sequence data in combination. New locality data and barcoding sequences are provided for other species of Coptoprepes, all endemic of the temperate forests of Chile and adjacent Argentina. Although morphology and sequences are not conclusive on the relationships of Coptoprepes species, the sequence data suggests that the species without a retrolateral tibial apophysis may belong to an independent lineage.